Prevalence of renal tuberculosis among patients presenting with active pulmonary tuberculosis in Ilorin - Nigeria - Chijioke, A; Aderibigbe, A (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Tuberculosis (TB) is a major healthproblem world-wide, especially in tropicaldeveloping countries involving major organs in thebody. The kidney is usually affected throughhaematogenous spread from a primary focus. Renaltuberculosis is the commonest form of extrapulmonary TB particularly among the Caucasians butthought to be rare in Blacks. Due to the paucity ofdata on the prevalence of renal TB. A prospectivestudy was undertaken to investigate the prevalence ofrenal TB in cases of active pulmonary TB (PTB) inllorin - Nigeria. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Confirmed cases of active PTB patients wereconsecutively recruited from the Pulmonary Clinicand the PTB Ward over a one year period. Theinclusion criteria were sputum acid fast baccili (AFB)positivity on two or more occasions and radiologicalevidence of PTB. Patients fullfilling the abovecriteria were investigated by urine analysis for sterileacid pyuria, Z-N stain, plain abdominal x-rays, renalultrasound, intravenous urogram and renal biopsy. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">A total of 148 acti ve PTB patients were studied (91males, 57 females). Male to female ratio was 3:2.The mean age of the males and females with renal TBwas 40 and 29 years respectively.The prevalence rates of AFB in urine and sterile acidpyuria were 9.5% and 8.8% respectively. Only 2.7%had both AFB in urine and sterile pyuria.Renal histology was abnormal in 70% of the biopsiedkidneys with sterile pyuria. The combination of AFBin urine and histologic evidence of renal TBincreased the prevalence of renal TB to 14% in thestudy. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">The study shows that renal TB in active PTB may be similar in Black and White populations. The diagnosis is difficult and a high index of clinical suspicion with combined diagnostic tools are required to identify the lesion.